F2RL3 methylation as a biomarker of current and lifetime smoking exposures - Zhang, Yan; Yang, Rongxi; Burwinkel, Barbara; Breitling, Lutz Philipp; Brenner, Hermann (Environmental health perspectives, 2014)
Background: Recent genome-wide DNA methylation studies have found a pronounced difference in methylation of the F2RL3 gene (also known as PAR-4) in blood DNA according to smoking exposure. Knowledge on the variation of F2RL3 methylation by various degrees of smoking exposure is still very sparse.Objectives: We aimed to assess dose-response relationships of current and lifetime active smoking exposure with F2RL3 methylation.Methods: In a large population-based study, we quantified blood DNA methylation at F2RL3 for 3,588 participants using matrix-assisted laser desorption ionization time-of-flight mass spectrometry. Associations of smoking exposure with methylation intensity were examined by multiple linear regression, controlling for potential confounding factors and paying particular attention to dose-response patterns with respect to current and lifetime smoking exposure as well as time since cessation of smoking.Results: F2RL3 methylation intensity showed a strong association with smoking status (p < 0.0001), which persisted after controlling for potential confounding factors. Clear inverse dose-response relationships with F2RL3 methylation intensity were seen for both current intensity and lifetime pack-years of smoking. Among former smokers, F2RL3 methylation intensity increased gradually from levels close to those of current smokers for recent quitters to levels close to never smokers for long-term (> 20 years) quitters.Conclusions: F2RL3 methylation is a promising biomarker for both current and long-term past tobacco exposure, and its predictive value for smoking-related diseases warrants further exploration.Citation: Zhang Y, Yang R, Burwinkel B, Breitling LP, Brenner H. 2014. F2RL3 methylation as a biomarker of current and lifetime smoking exposures. Environ Health Perspect 122:131-137;  http://dx.doi.org/10.1289/ehp.1306937